The “Three in One” Bone Repair Strategy for Osteoporotic Fractures - Chen, Xiao; Hu, Yan; Geng, Zhen; Su, Jiacan (Frontiers in Endocrinology, 2022)
In aging society, osteoporotic fractures have become one major social problem threatening the health of the elderly population in China. Compared with conventional fractures, low bone mass, bone defect and retarded healing issues of osteoporotic fractures lead to great difficulties in treatment and rehabilitation. Addressing major concerns in clinical settings, we proposed the “three in one” bone repair strategy focusing on anti-osteoporosis therapies, appropriate bone grafting and fracture healing accelerating. We summarize misconceptions and repair strategies for osteoporotic fracture management, expecting improvement of prognosis and clinical outcomes for osteoporotic fractures, to further improve therapeutic effect and living quality of patients.